2021
DOI: 10.3389/fchem.2021.629830
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Electrochemiluminescence of Halide Perovskites

Abstract: Halide perovskites are a rapidly developing class of solution-processable semiconductors which, to date, have a huge impact across several scientific communities. The remarkable photophysical attributes of halide perovskites illustrate their considerable potential in the electrochemiluminescence (ECL) realm. Over the past 4 years, great progress has been achieved in using halide perovskites as ECL emitters. In this mini-review, the basic characteristics, synthetic approaches, and ECL mechanisms for halide pero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…6 Later, a variety of ECL-active semiconductor nanocrystals spring up like mushrooms, such as II-VI compounds (e.g., CdS, CdSe), 7 carbon dots, 8 and the recently emerging halide perovskites. 9 In recent years, surging interest has emerged towards metal nanoclusters (MeNCs) as promising ECL candidates that are superior to foregoing emitters in many aspects, such as molecule-like nanostructure, atomic precision, stable optical and electrochemical properties, and low biological toxicity. [10][11][12] In 2009, Díez et al first reported the colour tunability and ECL phenomenon of few-atom silver nanoclusters (AgNCs), 13 which sets off an upsurge in fundamental ECL research and application of MeNCs.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…6 Later, a variety of ECL-active semiconductor nanocrystals spring up like mushrooms, such as II-VI compounds (e.g., CdS, CdSe), 7 carbon dots, 8 and the recently emerging halide perovskites. 9 In recent years, surging interest has emerged towards metal nanoclusters (MeNCs) as promising ECL candidates that are superior to foregoing emitters in many aspects, such as molecule-like nanostructure, atomic precision, stable optical and electrochemical properties, and low biological toxicity. [10][11][12] In 2009, Díez et al first reported the colour tunability and ECL phenomenon of few-atom silver nanoclusters (AgNCs), 13 which sets off an upsurge in fundamental ECL research and application of MeNCs.…”
Section: +mentioning
confidence: 99%
“…, CdS, CdSe), 7 carbon dots, 8 and the recently emerging halide perovskites. 9 In recent years, surging interest has emerged towards metal nanoclusters (MeNCs) as promising ECL candidates that are superior to foregoing emitters in many aspects, such as molecule-like nanostructure, atomic precision, stable optical and electrochemical properties, and low biological toxicity. 10–12…”
Section: Introductionmentioning
confidence: 99%
“…23 In recent years, the ECL technique has obtained remarkable attention in the development of biosensors due to its versatility and stability. 24,25 Moreover, the incorporation of different carbon-based nanomaterials has also aided the trend of using ECL methods in developing nanobiosensors. 26,27 The core mechanism of an ECL-based biosensor depends on the interaction between the luminophore and the target protein or antigen.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, due to substantial ionic salt properties, the PNCs even protected by oleic acid/oleylamine (OA/OAm) ligands will be dissolved rapidly in polar solvents or water as electrolytes under electrochemical conditions. Therefore, matrix encapsulation protocols to solve the instability problem and improve ECL performance for PNCs have been proposed by Zhu’s group, including SiO 2 matrix embedded by coreactants for self-enhancement and hollow carbon nitride nanosphere (HCNS) encapsulation as ratiometric ECL emitters. The outstanding and stable PNC ECL signals have been acquired with a conductive and functionalized shell as a firm framework, meanwhile providing pathways for electron–hole transfer and recombination. However, the preparation methods of these core–shell isolated structures are often time-consuming accompanied by tedious processes.…”
Section: Introductionmentioning
confidence: 99%